On the Identity of von Szily: Original Derivation and a New Proof - Larcombe, Peter J.; French, David R.; Gessel, Ira M. (Utilitas Mathematica, 2003)
The original derivation of a 19th century identity associated with K. von Szily is presented and discussed. An independent proof is given using a technique developed a decade or so later (by J. Dougall) in relation to hypergeometric function theory. For completeness, a historical backdrop is provided for the reader, together with other relevant information.